Bias in Scientific Research - Özdemir, Fatma (The Bulletin of Legal Medicine, 2023)
The aim of research is to find the “truth” in medicine. The researcher should be aware of the causes and characteristics of conscious and unconscious errors and know how to prevent them in order to reflect the “truth”. The value determined in epidemiological studies is the sum of: 1) Truth, 2) Random error, 3) Systematic error (Bias). In order to declare that the result is correct, errors must be excluded. Errors may arise at several stages in epidemiological research. Systematic errors lead to bias. In controlled studies, systematic errors often cause significant difference of one study group. However, “random error” or the chance factor does not cause bias. Since this type of error causes a deviation in both groups in the same direction, its effect is canceled, however the sensitivity of the results may decrease. Bias may be conscious or unconscious. A conscious bias is an intentional unethical act, made in order to achieve an intended result, ignoring scientific rules. Unconscious bias is due to inexperience of the researchers who do not consider the factors that may affect the results. Various errors may be made during epidemiological measurements. Since errors can never be eliminated, one should aim to minimize errors. Minimizing systematic errors increases the validity, and minimizing random errors increases power and accuracy of the studies. Bias results in incorrect diagnosis and management proposals, and waste of resources in studies that are carried out to diagnose health problems and to develop management strategies.